A new species of Chaeridiona Baly (Coleoptera: Chrysomelidae: Cassidinae: Oncocephalini) infesting ginger Zingiber officinale Roscoe) and turmeric (Curcuma longa L.) in India and redescription of Chaeridiona pseudometallica Basu - Shameem, K. M.; Prathapan, K. D. (Zootaxa, 2014)
Chaeridiona mayuri n. sp. infesting ginger (Zingiber officinale Roscoe) and turmeric (Curcuma longa L.) in southern India is described and illustrated. Cheilocostus speciosus ( J. Koenig) C. D. Specht, Globba sessiliflora Sims and Zingiber zerumbet (L.) Smith are reported as additional host plants. Chaeridiona pseudometallica Basu is redescribed and illustrated. A key to the species of Indian Chaeridiona is provided.